Die Calvinistiese onderwysleen Pedagogies normatief of anti-normatief? - Schoeman, S. (Hervormde teologiese studies, 1994)
The Calvinist doctrine of education: Pedagogically nomiative or antinormative? Each educational practice is an expression of an underlying doctrine of education, which in turn is grounded in a particular philosophy of life. The spotlight in this article falls on the Calvinist doctrine of education. The essence of this doctrine of education can be derived from its expression immediately adjacent to the lifetime of John Calvin (1509-1564). From a pedagogical evaluation of the Calvinist doctrine of education it becomes apparent that it is pedagogically justifiable and that it is in a position to make a positive contribution to education and teaching.